Alarm Systems in Buildings – Investigation of Effectiveness Depending on Building Type and User Profile - Gero Gerber (Communications - Scientific letters of the University of Zilina, 2020)
Alarm systems are used to warn passengers and employees in railway stations, airports, logistics facilities and administrative buildings of hazards; in this way, they are instructed to rescue themselves. A large online survey conducted in Germany in 2018 has shown that often sounding the alarm does not have the desired effect. The research presented in this article investigates dependence of an alarm effectiveness on type of building, user profile and type of the alarm system.In this paper, general and building-specific measures, using which the effective sounding of the alarm and optimal behaviour of the building users in the case of danger can be achieved, are presented.